Peningkatan Kemandirian dan Hasil Belajar Siswa Tingkat SMK Menggunakan Media Pembelajaran Genially: Improving Independence and Learning Outcomes of Vocational Level Students Using Genially Learning Media - Suspito, Maulana Aji; Churiyah, Madziatul; Arief, Mohammad; Basuki, Andi (Efektor, 2023)
Advances in modern technology have brought many changes to various lines of human life, one of which is education. The purpose of this research and development is to produce validated website-assisted learning media in order to improve learning outcomes and Student self-regulated learning. The development of learning media assisted by Website Genially is based on the limited learning media in the concentration of Office Management expertise, especially in meeting management material. This Research and Development uses the development model of Borg and Gall. The test subjects consisted of media and material experts, as well as class XI MPLB students at SMK Negeri 1 Boyolangu which were divided into small and large groups. The resulting research data is in the form of qualitative data and quantitative data. This study uses percentage descriptive analysis techniques, normality tests, and independent sample t-tests. The results of this research and development are in the form of Genially Website-assisted learning media by presenting gamification features and learning videos which have been declared very valid and feasible by expert validators and small group testing for use in learning activities and are able to improve learning outcomes and student self-regulated learning in the meeting management material.